Numerical Study of Solar Chimney with Absorber at Different Locations (Journal of Engineering, 2013)
Heat transfer process and fluid flow in a solar chimney used for natural ventilation are investigated numerically in the present work. Solar chimney was tested by selecting different positions of absorber namely: at the back side, front side, and at the middle of the air gap. CFD analysis based on finite volume method is used to predict the thermal performance, and air flow in two dimensional solar chimney under unsteady state condition, to identify the effect of different parameters such as solar radiation. Results show that a solar chimney with absorber at the middle of the air gap gives better ventilation performance. A comparison between the numerical and previous experimental results shows fair agreement.